2015
DOI: 10.1155/2015/371894
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior and Thermal Analysis of CoFeB Thin Films

Abstract: We examined two targets containing Co40Fe40B20and Co60Fe20B20. We deposited Co40Fe40B20and Co60Fe20B20monolayer thin films of various thicknesses on glass substrates through DC magnetron sputtering; the thicknesses ranged from 25 to 200 Å. The thermal properties of the Co40Fe40B20and Co60Fe20B20thin films were determined using a differential scanning calorimeter (DSC). The thermal properties included the glass transition temperature (Tg), onset crystallization temperature (Tx), and glass-forming ability, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This value is slightly larger than the value of 1.32 eV for crystallization of Co40Fe40B20 alloy films [34]. It confirms that thermal stability of Co60Fe40B20 is better than that of Co40Fe40B20 [37,38]. Additionally, the onset of temperature with rapid increasing resistivity in the high temperature region can also be fitted.…”
Section: Resultssupporting
confidence: 50%
“…This value is slightly larger than the value of 1.32 eV for crystallization of Co40Fe40B20 alloy films [34]. It confirms that thermal stability of Co60Fe40B20 is better than that of Co40Fe40B20 [37,38]. Additionally, the onset of temperature with rapid increasing resistivity in the high temperature region can also be fitted.…”
Section: Resultssupporting
confidence: 50%
“…The onset activation energy calculated of the Al 2 O 3 -GAP amorphous coating was 847.6 kJ/mol, which was greater than that of Al 2 O 3 -YAG amorphous coating. Figure 3b compares the initial crystallization activation energy obtained by the Kissinger method for some typical amorphous materials [22,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Conspicuously, the crystallization activation energy of the Al 2 O 3 -GAP amorphous coating reported in this work was higher than that of almost all amorphous materials, which indicated that it was extremely difficult to overcome the energy barrier to precipitate crystalline phase in the Al 2 O 3 -GAP amorphous coating.…”
Section: Thermal Stability Analysismentioning
confidence: 99%